High-Performance Perovskite Composite Electrocatalysts Enabled by Controllable Interface Engineering - Xu, Xiaomin; Pan, Y.; Ge, L.; Chen, Y.; Mao, X.; Guan, D.; Li, M.; Zhong, Yijun; Hu, Z.; Peterson, V.K.; Saunders, M.; Chen, C.T.; et al. (WILEY-V C H VERLAG GMBH, 2021)
Single-phase perovskite oxides that contain nonprecious metals have long been pursued as candidates for catalyzing the oxygen evolution reaction, but their catalytic activity cannot meet the requirements for practical electrochemical energy conversion technologies. Here a cation deficiency-promoted phase separation strategy to design perovskite-based composites with significantly enhanced water oxidation kinetics compared to single-phase counterparts is reported. These composites, self-assembled from perovskite precursors, comprise strongly interacting perovskite and related phases, whose structure, composition, and concentration can be accurately controlled by tailoring the stoichiometry of the precursors. The composite catalyst with optimized phase composition and concentration outperforms known perovskite oxide systems and state-of-the-art catalysts by 1–3 orders of magnitude. It is further demonstrated that the strong interfacial interaction of the composite catalysts plays a key role in promoting oxygen ionic transport to boost the lattice-oxygen participated water oxidation. These results suggest a simple and viable approach to developing high-performance, perovskite-based composite catalysts for electrochemical energy conversion.